Pharmacological Evaluation of the Recuperative Effect of Morusin Against Aluminium Trichloride (AlCl3)-Induced Memory Impairment in Rats - Gupta, Gaurav; Chellappan, Dinesh K.; Agarwal, Mohit; Ashwathanarayana, Madhu; Nammi, Srinivas; Pabreja, Kavita; Dua, Kamal (Central Nervous System Agents in Medicinal Chemistry, 2017)
Background: Elevation in brain levels of aluminium can be neurotoxic and can cause learning and memory deficiencies. In Chinese medicine, Morus alba is used as a neuroprotective herb. The current study was intended to discover the recuperative effect of morusin against aluminium trichloride (AlCl3)-induced memory impairment in rats along with biochemical mechanism of its protective action. Methods: Memory deficiency was produced by AlCl3 (100 mg/kg; p.o.) in experimental animals. Learning and memory activity was measured using Morris water maze (MWM) test model. Central cholinergic activity was evaluated through the measurement of brain acetylcholinesterase (AChE) activity. In addition to the above, oxidative stress was determined through assessment of brain thiobarbituric acid-reactive species (TBARS) and glutathione (GSH) levels. Results: AlCl3 administration prompted significant deficiency of learning and memory in rats, as specified by a noticeable reduction in MWM presentation. AlCl3 administration also produced a significant deterioration in brain AChE action and brain oxidative stress (increase in TBARS and decrease in GSH) levels. Treatment with morusin (5.0 and 10.0 mg/kg, dose orally) significantly overturned AlCl3- induced learning and memory shortages along with diminution of AlCl3-induced rise in brain AChE activity and brain oxidative stress levels. Conclusion: It may be concluded that morusin exerts a memory-preservative outcome in mental discrepancies of rats feasibly through its various activities.
Keywords: Acetylcholinestrase